Pine wilt disease in Europe - Mota, Manuel (2013)
In Europe, species of the nematode genus Bursaphelenchus have been known and studied for a long time (Fuchs 1937; Ruhm 1956). Earlier, except from a purely biological or ecological point of view, no particular interest was paid to this group of mycophagous nematodes. In 1979, however, a study conducted in southwestern France showed that the nematode Bursaphelenchus lignicolous was associated with declining pines (Baujard et al. 1979). This report caused alarm in Europe, since B. lignicolous is a synonym of B. xylophilus ; the nematode in question was later identifi ed as B. mucronatus (De Guiran et al. 1986), which had been described as a new species that year. In 1984, a shipment of wood from North America to Finland was found to carry the pine wood nematode (PWN), B. xylophilus (Rautapaa 1986). This important interception prompted European authorities to develop more rigorous inspections at sea ports, and in particular of wood products coming from North America. However, no equivalent emphasis was placed on such products coming from East Asia. Between 1996 and 1999, an EU-funded project (RISKBURS) resulted in an updated survey of the Bursaphelenchus species in Europe (European Communities 2003). For an updated situation on the species distribution in the EU, see Braasch (2001). In 1999, the PWN, the causal agent of pine wilt disease, was fi rst detected in the European Union (EU), in Portugal (Mota 2004; Mota et al. 1999), and this immediately prompted several national and EU governments to assess the extent of the nematode’s distribution, and to restrict B. xylophilus and its insect vector (Monochamus galloprovincialis ) to an area with a 30-km radius in the Setúbal Peninsula, 20 km south of Lisbon (Rodrigues 2007). The origin of the population of PWN found in Portugal remains unknown, although recent research indicates that it originated from Eastern Asia (Vieira et al. 2007). Several hypotheses have been suggested on how it entered the country, namely from North America or from Japan or China. World trade of wood products such as timber, wooden crates, and palettes play an important role in the potential dissemination of the PWN (Evans et al. 1996). In fact, human activities involving the movement of wood products may be the single most important factor in PWN spread. Despite the dedicated and concerted actions of government agencies, both the PWN and pine wilt disease continue to spread. In 2006 in Portugal, forestry and plant quarantine authorities (DGRF and DGPC) announced a new strategy for managing the problem. The plan is to establish a phytosanitary strip, 3-km wide, devoid of Pinus pinaster , surrounding the affected area, for the control and ultimately the eradication of the nematode, under the coordination of the national program for the control of the PWN (DGRF 2006). Research on the bioecology of the nematode and its insect vector, new detection methods, for example, involving real-time PCR, tree ecology and pathology, and control methods, has been underway since 1999. As well there are two major ongoing projects for the European Union (EU): PHRAME (http://www.forestresearch.gov.uk/website/forestresearch. nsf/ByUnique/INFD-63KGEF) and PortCheck (http://www.portcheck.eu.com/ index.cfm). This research has been instrumental in helping to understand the scientifi c aspects of pine wilt disease. The objective of the present paper is to highlight the progress made in Portugal and the EU. International agreements (GATT, WTO) and sharing of scientifi c information is of paramount importance for achieving effective control of the nematode and its vector, and in turn protection of our forest ecosystems and forest economies.